2008
DOI: 10.1007/s10706-008-9188-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress Analysis for Rock Mass Failure with Offset Joints

Abstract: Two-dimensional finite element model was created in this work to investigate the stress distribution within rock-like samples with offset open non-persistent joints under uniaxial loading. The results of this study have explained the fracture mechanisms observed in tests on rock-like material with open non-persistent offset joints (Mughieda and Alzo 'ubi, Geotech Geol Eng J 22:545-562, 2004). Finite element code SAP2000 was used to study the stresses distribution within the specimens. Fournoded isoperimetric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Mughieda and Omar [16] investigated the stress distribution of rock containing two fissures by using the finite element code with the name of SAP2000. The simulated results showed that tensile stress was mainly responsible for wing crack initiation while the shear stress was responsible for the a r c h i v e s o f c i v i l a n d m e c h a n i c a l e n g i n e e r i n g x x x ( 2 0 1 5 ) x x x -x x x a r t i c l e i n f o secondary crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Mughieda and Omar [16] investigated the stress distribution of rock containing two fissures by using the finite element code with the name of SAP2000. The simulated results showed that tensile stress was mainly responsible for wing crack initiation while the shear stress was responsible for the a r c h i v e s o f c i v i l a n d m e c h a n i c a l e n g i n e e r i n g x x x ( 2 0 1 5 ) x x x -x x x a r t i c l e i n f o secondary crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the fracture mechanism of rock engineering, many experimental and numerical investigations have been carried out on rocks containing various fissures (Lee and Jeon 2011;Li et al 2005;Mughieda and Omar 2008;Vásárhelyi and Bobet 2000;Wong and Einstein 2009;Yang et al 2012), which show that pre-existing fissures in natural rock masses have a great influence on their strength, deformation, and fracture coalescence behavior (Hall et al 2006;Lee and Jeon 2011;Li et al 2005;. Hall et al (2006) carried out an experimental study on natural and dry specimens of Neapolitan fine-grained tuff, and analyzed the crack coalescence processes of specimens containing one and two pre-existing fissures using acoustic emission (AE) and photographic monitoring, which were helpful to predict sudden and unexpected collapses of underground rock engineering.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of numerical methods, many simulation softwares have been adopted to analyze the crack coalescence processes of real rock material, including SAP2000 (Mughieda and Omar 2008), FROCK (Vásárhelyi and Bobet 2000), PFC 2D (Lee and Jeon 2011;, RFPA 2D (Tang 1997;Tang et al 1997), the boundary element method (BEM) (Chen et al 1998;Shen and Stephansson 1993;Shen 1995), cellular automata (CA) (Feng et al 2006;Pan et al 2009), and X-FEM (Colombo and Massin 2011;Grégoire et al 2007;Rozycki et al 2008). Mughieda and Omar (2008) investigated the stress distribution of rock containing two fissures using the finite element code SAP2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al (2001) developed some numerical methods to simulate the initiation and coalescence of flaws in rock-like materials, including the finite element method (FEM), boundary element method (BEM), and displacement discontinuity method (DDM), and Tang and Kou (1998) also proposed a new numerical code named Rock Failure Process Analysis (RFPA2D) to simulate the propagation and coalescence of cracks in a rock bridge area. In addition, the discrete element method (DEM) is also used to simulate the mechanical behavior of rock-like materials (Lee and Jeon 2011;Yang et al 2014;Manouchehrian et al 2014;Mughieda and Omar 2008). Fang and Harrison (2002a, b) adopted a degradation model to simulate the brittle failure in heterogeneous rocks.…”
Section: Introductionmentioning
confidence: 99%